Clinical Supervision as a Catalyst for Differentiated Instruction Implementation in Early Childhood Education - Norjannah, Norjannah; Ishartiwi, Ishartiwi (Journal of Innovation and Research in Primary Education, 2025)
Early childhood education requires differentiated learning approaches to address diverse student needs, yet kindergarten teachers often lack adequate support for implementing such practices. Clinical supervision offers a collaborative framework for professional development, but limited research examines its effectiveness in enhancing differentiated instruction implementation. This qualitative case study investigated clinical supervision implementation at TK Negeri Pembina Sangatta, East Kalimantan, Indonesia, from January to March 2025. Six participants including five classroom teachers and one principal-supervisor were involved through census sampling. Data collection employed in-depth interviews, classroom observations, and document analysis. Thematic analysis following the Miles and Huberman framework was conducted to identify patterns and themes related to clinical supervision processes and differentiated learning implementation. Clinical supervision followed a structured three-stage process comprising pre-conference, observation, and post-conference phases that created supportive professional development environments. Teachers developed enhanced competencies in designing tiered activities and adapting instruction across content, process, product, and learning environment dimensions. Key challenges included time constraints, resource limitations, and initial conceptual understanding gaps. Teachers demonstrated fundamental shifts in educational equity perspectives, moving from uniform to responsive teaching approaches. Effective supervisory strategies included reflective dialogue, evidence-based feedback, and ongoing coaching support. Findings align with clinical supervision theoretical frameworks emphasizing collaborative inquiry over evaluative assessment. The study addresses research gaps by demonstrating clinical supervision effectiveness in early childhood contexts and its role in facilitating complex pedagogical innovations. Results support professional development models emphasizing reflective practice and experiential learning while highlighting the importance of addressing systemic barriers for successful differentiated instruction implementation.